Problems with the upper limb in arthrogryposis. (December 2015) - Lester, Ruth
Introduction: This short paper presents a personal view of the thinking processes around the assessment and development of individualised management plans for dealing with the problems of the upper limb in Arthrogryposis in children. Background: The paper will offer a definition of arthrogryposis, its incidence and the range of anomalies. The problems associated with joint contractures are defined. The goals of treatment include improvement in function as well as cosmesis. Priorities and goals of treatment: Managing the mobility of the whole child is very important in deciding what should be offered surgically in the upper limb. Early manipulation and stretching as well as the pros and cons of splints are discussed. Principles of surgical procedures: The principles of surgery including soft tissue release, changing the position of the arc of movement of a joint, fixing stiff joints, tendon transfers and muscle transfers are presented. The value of thumb web release and the surgical procedures commonly used are described.